2015
DOI: 10.1158/1078-0432.ccr-14-2685
|View full text |Cite
|
Sign up to set email alerts
|

The MET Inhibitor AZD6094 (Savolitinib, HMPL-504) Induces Regression in Papillary Renal Cell Carcinoma Patient–Derived Xenograft Models

Abstract: Purpose: Papillary renal cell carcinoma (PRCC) is the second most common cancer of the kidney and carries a poor prognosis for patients with nonlocalized disease. The HGF receptor MET plays a central role in PRCC and aberrations, either through mutation, copy number gain, or trisomy of chromosome 7 occurring in the majority of cases. The development of effective therapies in PRCC has been hampered in part by a lack of available preclinical models. We determined the pharmacodynamic and antitumor response of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 35 publications
2
59
0
Order By: Relevance
“…Several compounds including small-molecule TKIs, monoclonal antibodies, and anti-HGF compounds are available for selective inhibition of MET signaling [48, 49] or inhibition of MET in combination with vascular endothelial growth factor receptor (VEGFR) [32, 50] and are already tested in preclinical and clinical trials [51], making anti-MET therapy a near-term feasible treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds including small-molecule TKIs, monoclonal antibodies, and anti-HGF compounds are available for selective inhibition of MET signaling [48, 49] or inhibition of MET in combination with vascular endothelial growth factor receptor (VEGFR) [32, 50] and are already tested in preclinical and clinical trials [51], making anti-MET therapy a near-term feasible treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we describe a patient with metastatic NSCLC with MET-mediated resistance to EGFR TKI who responded to treatment with a type I MET inhibitor, savolitinib (11), given in combination with a third-generation EGFR inhibitor, osimertinib (2). The patient then developed acquired resistance mediated by a novel MET kinase domain mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Although patients with sporadic RCC of any histological subtype usually show a good clinical outcome, patients with metastatic pRCC show a significantly worse clinical course than patients with ccRCC or chromophobe RCC [24]. Recent findings have indicated that MET gene activation, which is known to promote proliferative activity and cell survival, is frequently observed in pRCC, and MET inhibitors have become a new type of therapeutic agent for patients with advanced pRCC [5, 6]. …”
Section: Introductionmentioning
confidence: 99%